2017
DOI: 10.1108/jsit-01-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

Roles of self-monitoring, fashion involvement and technology readiness in an individual’s propensity to use mobile shopping

Abstract: Purpose This paper aims to investigate the relationships between self-monitoring, fashion involvement and technology readiness in the mobile shopping context. Although mobile shopping is still a novel activity in Turkish economical and social spheres, it has the potential to become an important driver of B2C electronic commerce in Turkey. Many Turkish firms have already extended their multichannel strategies by integrating a mobile channel into their pre-existing on-line and off-line channels. However, custome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 69 publications
5
21
0
Order By: Relevance
“…In our results, it was shown that fashion involvement moderated the path from technology attitudes to purchase intention, but not the path from attitudes toward AI to purchase intention. These results are consistent with previous studies in that consumers of higher fashion involvement are more likely to be ready to use new technology (Celik & Kocaman, 2017); however, they are not quite ready to purchase the fashion AI product. Perhaps they are waiting for more customer reviews and a newer version with improved functions or performance of this one of a kind product.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our results, it was shown that fashion involvement moderated the path from technology attitudes to purchase intention, but not the path from attitudes toward AI to purchase intention. These results are consistent with previous studies in that consumers of higher fashion involvement are more likely to be ready to use new technology (Celik & Kocaman, 2017); however, they are not quite ready to purchase the fashion AI product. Perhaps they are waiting for more customer reviews and a newer version with improved functions or performance of this one of a kind product.…”
Section: Discussionsupporting
confidence: 92%
“…Consumers of higher level fashion involvement value fashion clothing more, are less price-sensitive, and are more engaged in fashion-related activities such as seeking out fashion news and trying new fashion-related technologies (Naderi, 2013; Yanshu & Guo, 2017). Celik and Kocaman (2017) concluded that fashion involvement has significant and direct influences on technology readiness. It is assumed that consumers with higher fashion involvement will be more likely to enjoy the interaction with the AI product.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…This study defines omni-channel shoppers as those who use multiple channels (physical stores, websites, and mobile apps) of the same retailer spontaneously during a single shopping journey. Previous studies have suggested that fashion innovativeness and purchase involvement are significant personal traits of fashion consumers (Cardoso, Costa, & Novais, 2010;Cho & Workman, 2011;Ryu, 2011), and technology innovativeness is an important predictor for consumers' online or mobile shopping intentions (Celik & Kocaman, 2017;Lu, 2014). Thus, the present study uses these consumer characteristics --fashion innovativeness, technology innovativeness, and fashion purchase involvement --as determinants predicting consumers' omnichannel shopping intentions for fashion products.…”
Section: Introductionmentioning
confidence: 88%
“…In the retailing context, omni-channel shopping can be viewed as the latest technology-based system, as it involves mobile technology and the integration of different channel options to create seamless shopping environment from start to finish. A reasonable number of studies have investigated the influence of technology innovativeness on consumer adoption of new technology-based shopping options and confirmed that a positive and significant relationship exists between the two (Ba g ze, 2015; Boyle & Ruppel, 2006;Celik & Kocaman, 2017;Mummalaneni, Meng, & Elliott, 2016). Consumers with a higher level of technology innovativeness tend to use mobile-based sources for product search and product information (Jai & Tung, 2015).…”
Section: Technology Innovativenessmentioning
confidence: 99%
“…Multifaceted trust-risk model and theory of planned behaviour jointly occupied fourth position by serving as theoretical lens on two instances each. Furthermore, there were eight theories/models such as (1) 4P's marketing theory [16], (2) Behavioural reasoning theory [37], (3) Elaboration likelihood model [38], (4) Flow theory [39], (5) IS success model [14], (6) Stimulus-Organism-Response (SOR) framework [40], (7) Technology readiness [41], and (8) Trust transfer theory [15] that researchers employed on one instance each. Finally, there were two studies [42,43] that did not employ any dominant theories to examine consumer mobile shopping acceptance.…”
Section: Dominant Theories/modelsmentioning
confidence: 99%